Penilaian Sikap Pada Mata Pelajaran Pendidikan Agama Islam - Adha, Fadhilah; Rivauzi, Ahmad (An-Nuha, 2024)
Various subjects given in formal education, one of which is the subject of Islamic Religious Education given to every level of education, the purpose of this study is to collect data on how PAI teachers at SD Negeri 15 Lubuk Alung Planning, Implementation, and Reporting and Processing the results of the assessment of students' spiritual and social attitudes. This research determines qualitative research methods through various field research. To obtain interview results, this study used interview guidelines as a research instrument. The data collection techniques used are observation (observation), interview (interview), documentation, and a combination of the three. While the data analysis technique that the author uses is an interactive model qualitative approach consisting of three stages, namely data reduction, data presentation and conclusion drawing or verification. Overall the results of this study indicate; First, the Islamic Religious Education Teacher of SD Negeri 15 Lubuk Alung organizes moral recommendations and social conditions in accordance with the existing plan referring to Permendikbud No. 23 of 2016 concerning Calculation. And the Islamic Religious Education Teacher makes the decision to evaluate spiritual attitudes and social attitudes in accordance with the KI and KD mentioned in the reference, in determining indicators of the characteristics of spiritual attitudes and social attitudes and revealing them to students as soon as possible. to determine the procedure. and attitude assessment tools. The techniques used in attitude assessment are observation, self-assessment, and peer assessment. In its implementation, the teacher also uses observation techniques, while the peer evaluation method, although developed, has not been implemented properly. Second, the implementation of attitude assessment of community values and morals in Islamic religious education subjects at SD Negeri 15 Lubuk Alung has been carried out but not well because there are still differences between the implementation and design of the lesson plan. Regarding the counseling techniques used, in the lesson plan the counseling techniques used are personal counseling and peer counseling. While in its implementation, PAI teachers use observation techniques in the form of journals. This is related to the obstacles faced by teachers, namely the limited time to conduct assessments, as a result not all aspects of affective and social behavior can be assessed. Third, the level of points given depends on what is used. If the assessment uses a scale then it uses points, but if it uses observation techniques or observations with journal assessment tools it does not use points.